2009
DOI: 10.1177/1524838009334130
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Asian Immigrant Communities

Abstract: Intimate partner violence (IPV) is a serious epidemic among Asian immigrant communities. Yet little is known about the scope, nature, and related contextual, cultural, and social factors of IPV among this population. In particular, the lack of research has been evident in examining health and mental health outcomes of IPV and service utilization, revealing notable gaps in health disparities which result in a failure to provide relevant services and law enforcement protection for battered Asian immigrant women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(74 citation statements)
references
References 170 publications
(182 reference statements)
3
70
0
1
Order By: Relevance
“…When a female fails to meet societal expectations or to perform her duties, violence is reckoned as a valid alternative to educate her. Many states in the Muslim world adopt laws and regulations enforcing patriarchal values that give men the responsibility to decide for their female family members while cultural attitudes regarding the social acceptance of violence are widespread (Lee & Hadeed, 2009) and may also be legitimized by a literal interpretation of the Qur’an. This results in different degrees of acceptance of violent behaviors and their normalization in social and intimate relationships: violence may be considered a normative, not deviant, behavior to discipline dependent family members (Ibrahim & Abdalla, 2010).…”
Section: Muslim Immigrants’ Attitudes Towards Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…When a female fails to meet societal expectations or to perform her duties, violence is reckoned as a valid alternative to educate her. Many states in the Muslim world adopt laws and regulations enforcing patriarchal values that give men the responsibility to decide for their female family members while cultural attitudes regarding the social acceptance of violence are widespread (Lee & Hadeed, 2009) and may also be legitimized by a literal interpretation of the Qur’an. This results in different degrees of acceptance of violent behaviors and their normalization in social and intimate relationships: violence may be considered a normative, not deviant, behavior to discipline dependent family members (Ibrahim & Abdalla, 2010).…”
Section: Muslim Immigrants’ Attitudes Towards Ipvmentioning
confidence: 99%
“…More specifically, immigrant couples coming from majority-Muslim countries show higher IPV rates if compared to their non-immigrant counterparts: for example, Moroccan immigrant women in Spain (Colorado-Yohar et al, 2012), Iraqi (Barkho, Fakhouri, & Arnetz, 2011), as well as Pakistani and South-Asian (Adam & Schewe, 2007; Lee & Hadeed, 2009) women immigrated to the U.S. report being exposed to abusive behaviors to a greater extend if compared to the native population and even to other non-immigrant Muslim women.…”
mentioning
confidence: 99%
“…Particularly, a review of DV among Asian immigrant communities indicated that patriarchal beliefs were consistently associated with increased DV (Y. S. Lee & Hadeed, 2009). However, other studies found that immigrant women's traditional gender role beliefs were associated with less DV (Firestone, Harris, & Vega, 2003), because DV can be intensified due to changes in gender roles and power dynamics after resettlement in a host country (Yick, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These differences are related to both sexes and may suggest that the patriarchal model should be seen as still prevalent. Patriarchal power is present through all the social organizations and it influences the way each person thinks about him/herself and takes a position according to that sex and gender system (Bui & Morash 2008;Hunnicut, 2009;Lee & Hadeed, 2009;Lindhorst & Tajima, 2008); the power inequalities and established unbalance by which men tend to dominate women. Moreover, even when within a same-sex couple this is expected to be more "equal" in context than in the heterosexual couples, men and women appeared to believe that GM are more physical violent than LW.…”
Section: Discussionmentioning
confidence: 99%